Preparation method of far-end access catheter for nerve intervention
By modifying polytetrafluoroethylene and nitinol alloy on the inner wall of the distal passage catheter and combining with hyaluronic acid grafted modified polyurethane outer layer, the problems of insufficient hydrophobicity and poor biocompatibility of the catheter are solved, and higher stability and safety are achieved.
Patent Information
- Application Number
- CN202411984506.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing distal pathway catheters have problems of insufficient hydrophobicity and poor biocompatibility during neurointervention, which affects their stability and safety in the blood vessels.
By modifying PTFE on the inner wall of the catheter, a micro-nano rough structure is formed to improve hydrophobic properties, and a laser beam is used to irradiate the nickel-titanium alloy to enhance its strength. At the same time, hyaluronic acid grafted to modify the polyurethane outer layer to improve the biocompatibility and hydrophilicity of the catheter.
It improves the hydrophobic performance and biocompatibility of the catheter, enhances its stability and safety in the blood vessels, and is suitable for distal access catheters for neural intervention.
Smart Images

Figure CN119746172A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical equipment and relates to a distal access catheter, and in particular to a distal access catheter for neurointervention. Background Art
[0002] Distal access catheters can be used in neurovascular, coronary, and peripheral vascular systems, and are applicable to a wide range of scenarios. In clinical practice, it is often used as a guide catheter to transmit other interventional diagnostic or surgical instruments to designated locations on the blood vessels; it can also be used as an angiography catheter to infuse contrast agents for angiography; in addition, it can also be used as an aspiration catheter to attract thrombi with negative pressure. Especially in stroke treatment, the advantages of distal access catheters are obvious. For example, when treating ischemic stroke, if the thrombus is located far away from the brain, the distal access catheter can be well followed up by the micro-guidewire and micro-catheter, and negative pressure attraction can be performed after reaching the starting site of the thrombus. At the same time, the thrombectomy stent can be delivered for combined treatment. With the continuous development and popularization of interventional technology, the market demand for distal access catheters continues to increase. Especially in China, according to the "China Cardiovascular Health and Disease Report 2021", there are a large number of people suffering from cardiovascular diseases in my country, among which the incidence of diseases such as stroke and coronary heart disease remains high. This provides a broad market space for interventional medical devices such as distal access catheters. At the same time, the strength of domestic interventional medical device companies continues to improve, the number of domestically produced distal access catheters approved for marketing is gradually increasing, and market competition is becoming increasingly fierce. Summary of the invention
[0003] In view of the above problems, the present invention designs a distal access catheter for neurointervention; the catheter specifically comprises the following steps:
[0004] S1. Modified polytetrafluoroethylene: weigh 0.4-1.0g polyethylene oxide (PEO) and add it to 40ml polytetrafluoroethylene emulsion with a mass fraction of 20%, and then stir it magnetically at room temperature for 12 hours to form a mixed emulsion; apply the mixed emulsion to the upper surface of the metal tube core rod through an electrostatic spinning machine, with a coating thickness of 20-50um, place it in an oven at 40°C for 12 hours to dry it for preliminary shaping, and then transfer it to a muffle furnace at 170-200°C for sintering for 2-5 hours; after sintering, wrap the outer surface of the polytetrafluoroethylene coating with a spring layer, which is formed by extruding molten silicone rubber rollers and has a thickness of 30-40um; the addition of polyethylene oxide reduces the surface properties of the polytetrafluoroethylene coating and forms a micro-nano rough structure, which improves the hydrophobicity of the inner wall of the tube;
[0005] S2. A 20-30um nickel-titanium alloy wire is irradiated with a laser beam to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, and at the same time improving the strength of the alloy. The laser parameters are a wavelength of 1000nm, a frequency of 50Hz, and a power of 5-20W. The high-intensity plasma shock wave generated by the strong laser beam is continuously applied to the sample surface to cause plastic deformation of the alloy surface, reshaping the state of the alloy surface and making it have higher strength.
[0006] S3, the outer layer of the spring layer in step S1 is reinforced by cross-weaving the nickel-titanium alloy metal coil prepared in step S2 through a braiding machine, and after reinforcement, the metal tube core rod is extruded by an online extruder, and at the same time, the surface is extruded by a pair of rollers at the rear end of the extrusion, and the molten aliphatic polyurethane outer layer is wrapped on the surface of the nickel-titanium alloy during the online extrusion, and the thickness of the polyurethane layer is 60-75um; the pair of rollers reduces the gaps and processing defects inside the catheter, and the combination of polyurethane and the nickel-titanium alloy coil after laser beam irradiation not only makes the catheter have good mechanical strength but also softness;
[0007] S4, hyaluronic acid grafting modification: 0.4-1.0 ml of 0.1-0.4 mmol N, N'-dimethylaminoethylcarbodiimide solution was added dropwise to 20 ml of 0.5-1.1 mol / L sodium citrate aqueous solution, and the openings of the catheter prepared in step S3 were sealed with clay, and then immersed in the solution, and immersed for 4-7 hours at a constant temperature of 30-60 ° C, and then 0.4-1.0 ml of 1,3-propylenediamine was added to the solution and continued to be immersed for 4-7 hours. After that, the outer layer of the catheter was fully rinsed three times with deionized water, and the washed catheter was placed in a vacuum drying oven at 40 ° C to dry. The purpose of this process is to amino the polyurethane on the outer surface; the dried catheter was immersed in 20 ml of 1-4 g hyaluronic acid and 0.4-1.0 ml of 0.1-0.4 mmol N, N'-dimethylaminoethylcarbodiimide solution. The distal access catheter with a polyurethane outer layer grafted with hyaluronic acid is obtained by placing the catheter in a 0.5-1.1 mol / L sodium citrate solution for 4-7 hours, then ultrasonically cleaning it with deionized water for 5 minutes and drying it in a vacuum drying oven at 40°C; N,N'-dimethylaminoethylcarbodiimide reacts with polyurethane with carboxyl groups to generate an unstable intermediate, which combines with the protonated carboxyl groups in the hyaluronic acid molecules to form an amide bond, thereby grafting the hyaluronic acid onto the polyurethane surface; the grafted distal access catheter surface has better biocompatibility;
[0008] S5. The distal access catheter prepared in S4 is sterilized with ethylene oxide to obtain a distal access catheter for neurointervention.
[0009] Preferably, in step S1, 0.6 g of polyethylene oxide (PEO) is weighed;
[0010] Preferably, the thickness of the polytetrafluoroethylene coating in step S1 is 40 um;
[0011] Preferably, the sintering in the step S1 is carried out in a muffle furnace at 200° C.;
[0012] Preferably, in step S2, a 30 um nickel-titanium alloy wire is used;
[0013] Preferably, the thickness of the polyurethane layer in step S3 is 70 um;
[0014] Preferably, in step S4, the amount of N,N'-dimethylaminoethylcarbodiimide added is 0.8 ml;
[0015] Preferably, in step S4, the mixture is immersed at a constant temperature of 60° C. for 5 hours;
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The present invention uses polyethylene oxide to modify polytetrafluoroethylene so as to improve the hydrophobicity of polytetrafluoroethylene. The addition of polyethylene oxide reduces the surface properties of the polytetrafluoroethylene coating and forms a micro-nano rough structure, which improves the hydrophobicity of the inner wall of the tube.
[0018] 2. The present invention uses a laser beam to irradiate nickel-titanium alloy to cause the metal wire to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, while improving the strength of the alloy; the high-intensity plasma shock wave generated by the strong laser beam is continuously applied to the sample surface to cause plastic deformation of the alloy surface, reshaping the state of the alloy surface and giving it higher strength.
[0019] 3. The present invention grafts hyaluronic acid to modify the polyurethane outer layer catheter; N,N'-dimethylaminoethylcarbodiimide reacts with polyurethane with carboxyl groups to generate an unstable intermediate, and the intermediate combines with the protonated carboxyl groups in the hyaluronic acid molecules to form an amide bond, thereby grafting the hyaluronic acid onto the polyurethane surface; the surface of the distal access catheter after grafting has better biocompatibility and hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the inner surface of the polytetrafluoroethylene inner tube prepared in step S1 in Example 1 of the present invention.
[0021] Figure 2 This is a laser confocal micrograph of bEnd.3 cells in Example 3 of the present invention.
[0022] Figure 3 This is a laser confocal micrograph of bEnd.3 cells in Comparative Example 7 of the present invention.
[0023] Figure 4 This is a laser confocal micrograph of bEnd.3 cells in Comparative Example 8 of the present invention. DETAILED DESCRIPTION
[0024] Exemplary embodiments, features and performance aspects of the present invention will be described in detail below with reference to the accompanying drawings.
[0025] In the present invention, polyethylene oxide (PEO) was purchased from Shanghai McLean Biochemical Technology Co., Ltd.; 20% polytetrafluoroethylene emulsion was purchased from Jiangxi Zhongfu Chemical Material Technology Co., Ltd.; metal tube core rod with a diameter of 0.096 inches was purchased from Wuxi Hongxin Special Steel Co., Ltd.; lignin was purchased from Bashifu (Shanghai) Biomedical Technology Co., Ltd.; epoxy resin was purchased from Jiangsu Bost Chemical Technology Co., Ltd.; polyvinyl alcohol was purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0026] Example 1
[0027] S1. Modified polytetrafluoroethylene: 0.4g polyethylene oxide (PEO) was weighed and added to 40ml polytetrafluoroethylene emulsion with a mass fraction of 20%, and then magnetically stirred at room temperature for 12 hours to form a mixed emulsion; the mixed emulsion was coated on the upper surface of the metal tube core rod through an electrostatic spinning machine, and the coating thickness was 20um, and it was placed in an oven at 40°C for 12 hours to be initially shaped, and then transferred to a muffle furnace at 170°C for sintering for 2 hours; after sintering, a spring layer was wrapped on the outer surface of the polytetrafluoroethylene coating, and the spring layer was formed by extruding molten silicone rubber rollers, and the thickness was 30um; the addition of polyethylene oxide reduced the surface properties of the polytetrafluoroethylene coating and formed a micro-nano rough structure, which improved the hydrophobicity of the inner wall of the tube;
[0028] S2. A 20um nickel-titanium alloy wire is irradiated with a laser beam to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, and at the same time improving the strength of the alloy. The laser parameters are a wavelength of 1000nm, a frequency of 50Hz, and a power of 5W. The high-intensity plasma shock wave generated by the strong laser beam is continuously applied to the surface of the nickel-titanium alloy to cause it to undergo plastic deformation, reshape the state of the alloy surface and make it have higher strength.
[0029] S3, the outer layer of the spring layer in step S1 is reinforced by cross-weaving the nickel-titanium alloy metal coil prepared in step S2 through a braiding machine, and after reinforcement, the metal tube core rod is extruded by an online extruder, and at the same time, the surface is extruded by a pair of rollers at the rear end of the extrusion, and the molten aliphatic polyurethane outer layer is wrapped on the surface of the nickel-titanium alloy during the online extrusion, and the thickness of the polyurethane layer is 60um; the pair of rollers reduces the gaps and processing defects inside the catheter, and the combination of polyurethane and the nickel-titanium alloy coil after laser beam irradiation not only makes the catheter have good mechanical strength but also softness;
[0030] S4, hyaluronic acid grafting modification: 0.4 ml of 0.1 mmol N, N'-dimethylaminoethylcarbodiimide solution was added dropwise to 20 ml of 0.5 mol / L sodium citrate aqueous solution, and then the outer wall of the catheter prepared in step S3 was immersed in the solution, and immersed at a constant temperature of 30°C for 4 hours, and then 0.4 ml of 1,3-propylenediamine was added to the solution and immersed for another 4 hours, and then the outer layer of the catheter was fully rinsed three times with deionized water. The washed catheter was placed in a vacuum drying oven at 40°C for drying. The purpose of this process is to amino the polyurethane on the outer surface; the amino outer polyurethane was immersed in 20 ml of 1 g hyaluronic acid and 0.4 ml of 0.1 mmol N, N'-dimethylaminoethylcarbodiimide solution. The hyaluronic acid was grafted onto the polyurethane outer layer catheter after being placed in a 0.5 mol / L sodium citrate solution for 4 hours, then ultrasonically cleaned with deionized water for 5 minutes and dried in a vacuum drying oven at 40°C; N,N'-dimethylaminoethylcarbodiimide reacted with the polyurethane with carboxyl groups to generate an unstable intermediate, which combined with the protonated carboxyl groups in the hyaluronic acid molecules to form an amide bond, thereby grafting the hyaluronic acid onto the polyurethane surface; the grafted distal access catheter surface had better biocompatibility;
[0031] S5. The distal access catheter prepared in S4 is sterilized with ethylene oxide to obtain a distal access catheter for neurointervention.
[0032] Comparative Example 1: Except that lignin is used instead of polyethylene oxide in step S1, the other steps are the same as those in Example 1.
[0033] Comparative Example 2: Except that epoxy resin is used instead of polyethylene oxide in step S2, the other steps are the same as those in Example 1.
[0034] Comparative Example 3: Except that polyvinyl alcohol is used instead of polyethylene oxide in step S2, the other steps are the same as those in Example 1.
[0035] Take the sintered polytetrafluoroethylene inner tube in S1 and press it flat and place it on a glass slide. Fix the side of the catheter with tape, adjust the position of the injection needle to the middle of the catheter, and drop 5uL of deionized water onto the catheter surface by the suspension method to measure the static water contact angle of the surface. Five different test points were selected for each sample for testing, and the contact angle was recorded with a camera. The results are shown in Table 1.
[0036] Table 1
[0037] project Water contact angle / (°) Example 1 135.9±5.67 Comparative Example 1 110.4±4.44 Comparative Example 2 112.1±3.21 Comparative Example 3 108.5±5.59
[0038] It can be seen from Table 1 that the contact angle of polytetrafluoroethylene modified with polyethylene oxide is greatly improved compared with the polytetrafluoroethylene in comparative example 1. This is mainly because polyethylene oxide connects the polytetrafluoroethylene particles together and thus better reduces the surface properties of polytetrafluoroethylene during the sintering process and forms a micro-nano structure such as Figure 1 As shown, the particles are dispersed more evenly. The water contact angle of using epoxy resin and polyvinyl alcohol to replace polyethylene oxide is significantly lower than that of Example 1, mainly because of its good water dispersibility, which can better connect the polytetrafluoroethylene particles.
[0039] Example 2
[0040] S1. Modified polytetrafluoroethylene: 0.6g polyethylene oxide (PEO) was weighed and added to 40ml of 20% polytetrafluoroethylene emulsion, and then magnetically stirred at room temperature for 12h to form a mixed emulsion; the mixed emulsion was coated on the upper surface of the metal tube core rod through an electrostatic spinning machine, and the coating thickness was 30um, and it was placed in an oven at 40°C for 12h for initial shaping and then transferred to a muffle furnace at 180°C for sintering for 3h; after sintering, a spring layer was wrapped on the outer surface of the polytetrafluoroethylene coating, and the spring layer was formed by extrusion of molten silicone rubber rollers, and the thickness was 30um; the addition of polyethylene oxide reduced the surface properties of the polytetrafluoroethylene coating and formed a micro-nano rough structure, which improved the hydrophobicity of the inner wall of the tube;
[0041] S2. A 20um nickel-titanium alloy wire is irradiated with a laser beam to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, and at the same time improving the strength of the alloy. The laser parameters are a wavelength of 1000nm, a frequency of 50Hz, and a power of 15W. The high-intensity plasma shock wave generated by the strong laser beam is continuously applied to the surface of the nickel-titanium alloy to cause it to undergo plastic deformation, reshape the state of the alloy surface and make it have higher strength.
[0042] S3, the outer layer of the spring layer in step S1 is reinforced by cross-weaving the nickel-titanium alloy metal coil prepared in step S2 through a braiding machine, and after reinforcement, the metal tube core rod is extruded by an online extruder, and at the same time, the surface is extruded by a pair of rollers at the rear end of the extrusion, and the molten aliphatic polyurethane outer layer is wrapped on the surface of the nickel-titanium alloy during the online extrusion, and the thickness of the polyurethane layer is 65um; the pair of rollers reduces the gaps and processing defects inside the catheter, and the combination of polyurethane and the nickel-titanium alloy coil after laser beam irradiation not only makes the catheter have good mechanical strength but also softness;
[0043] S4, hyaluronic acid grafting modification: 0.6 ml of 0.2 mmol N, N'-dimethylaminoethylcarbodiimide solution was added dropwise to 20 ml of 0.7 mol / L sodium citrate aqueous solution, and then the outer wall of the catheter prepared in step S3 was immersed in the solution, immersed at a constant temperature of 40°C for 5 hours, and then 0.6 ml of 1,3-propylenediamine was added to the solution and immersed for another 5 hours, and then the outer layer of the catheter was fully rinsed three times with deionized water. The washed catheter was placed in a vacuum drying oven at 40°C for drying. The purpose of this process is to amino the polyurethane on the outer surface; the amino outer polyurethane was immersed in 20 ml of 2 g hyaluronic acid and 0.6 ml of 0.2 mmol N, N'-dimethylaminoethylcarbodiimide solution. The hyaluronic acid was grafted onto the polyurethane outer layer catheter after being placed in a 0.7 mol / L sodium citrate solution for 5 hours, then ultrasonically cleaned with deionized water for 5 minutes and dried in a vacuum drying oven at 40°C; N,N'-dimethylaminoethylcarbodiimide reacted with the polyurethane with carboxyl groups to generate an unstable intermediate, which combined with the protonated carboxyl groups in the hyaluronic acid molecules to form an amide bond, thereby grafting the hyaluronic acid onto the polyurethane surface; the grafted distal access catheter surface had better biocompatibility;
[0044] S5. The distal access catheter prepared in S4 is sterilized with ethylene oxide to obtain a distal access catheter for neurointervention.
[0045] Comparative Example 4: Except that nickel-titanium alloy is not used in step S2, the remaining steps are the same as those in Example 2.
[0046] Comparative Example 5: Except for using magnesium alloy instead of nickel-titanium alloy in step S2, the remaining steps are the same as those in Example 2.
[0047] Comparative Example 6: Except that the laser beam is not used to irradiate the nickel-titanium alloy in step S2, the remaining steps are the same as those in Example 2.
[0048] Flattening tests were performed on Example 2, Comparative Example 4, Comparative Example 5 and Comparative Example 6 respectively. When performing the flattening test, the distal passage catheter was placed between two parallel plates and pressed down evenly with a press to observe whether it was deformed. The power of the press was 5.5KW, the pressing speed was 50um / s, and the fixed load was 20N. The results are shown in Table 2.
[0049] It can be seen from Table 2 that in the fixed load pressure test, the nickel-titanium alloy irradiated by laser can still maintain the original appearance of the catheter and will not be significantly deformed. Comparative Example 5 using magnesium alloy cannot maintain the original appearance of the catheter, and Comparative Example 4 not using nickel-titanium alloy is directly flattened. It can be seen that the nickel-titanium alloy as the supporting layer of the catheter protects the original appearance of the catheter very well and has stronger compressive resistance. At the same time, Example 2 and Comparative Example 6 show that the nickel-titanium alloy irradiated by laser has stronger compressive resistance, which is mainly due to the high-intensity plasma shock wave generated by the strong laser beam continuously applied to the surface of the nickel-titanium alloy to cause plastic deformation, reshape the state of the alloy surface and make it have higher strength.
[0050] Table 2
[0051] project Downward pressure load / N Catheter appearance Example 1 20 No obvious change, keep the round shape Comparative Example 4 20 The catheter is flattened Comparative Example 5 20 The catheter becomes oval Comparative Example 6 20 Slightly deformed, but cannot maintain a round shape
[0052] Example 3
[0053] S1. Modified polytetrafluoroethylene: 0.8g polyethylene oxide (PEO) was weighed and added to 40ml polytetrafluoroethylene emulsion with a mass fraction of 20%, and then magnetically stirred at room temperature for 12 hours to form a mixed emulsion; the mixed emulsion was coated on the upper surface of the metal tube core rod through an electrostatic spinning machine, and the coating thickness was 40um, and it was placed in an oven at 40°C for 12 hours to be initially shaped and then transferred to a muffle furnace at 190°C for sintering for 4 hours; after sintering, a spring layer was wrapped on the outer surface of the polytetrafluoroethylene coating, and the spring layer was formed by extruding molten silicone rubber rollers, and the thickness was 40um; the addition of polyethylene oxide reduced the surface properties of the polytetrafluoroethylene coating and formed a micro-nano rough structure, which improved the hydrophobicity of the inner wall of the tube;
[0054] S2. A 30um nickel-titanium alloy wire is irradiated with a laser beam to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, and at the same time improving the strength of the alloy. The laser parameters are a wavelength of 1000nm, a frequency of 50Hz, and a power of 10W. The high-intensity plasma shock wave generated by the strong laser beam is continuously applied to the surface of the nickel-titanium alloy to cause it to undergo plastic deformation, reshape the state of the alloy surface and make it have higher strength.
[0055] S3, the outer layer of the spring layer in step S1 is reinforced by cross-weaving the nickel-titanium alloy metal coil prepared in step S2 through a braiding machine, and after reinforcement, the metal tube core rod is extruded by an online extruder, and at the same time, the surface is extruded by a pair of rollers at the rear end of the extrusion, and the molten aliphatic polyurethane outer layer is wrapped on the nickel-titanium alloy surface during the online extrusion, and the thickness of the polyurethane layer is 70um; the pair of rollers reduces the gaps and processing defects inside the catheter, and the combination of polyurethane and the nickel-titanium alloy coil after laser beam irradiation not only makes the catheter have good mechanical strength but also has softness;
[0056] S4, hyaluronic acid grafting modification: 0.8 ml of 0.3 mmol N, N'-dimethylaminoethylcarbodiimide solution was added dropwise to 20 ml of 0.9 mol / L sodium citrate aqueous solution, and then the outer wall of the catheter prepared in step S3 was immersed in the solution, immersed at a constant temperature of 50°C for 6 hours, and then 0.8 ml of 1,3-propylenediamine was added to the solution and immersed for another 6 hours, and then the outer layer of the catheter was fully rinsed three times with deionized water. The washed catheter was placed in a vacuum drying oven at 40°C for drying. The purpose of this process is to amino the polyurethane on the outer surface; the amino outer polyurethane was immersed in 20 ml of 3 g hyaluronic acid and 0.8 ml of 0.3 mmol N, N'-dimethylaminoethylcarbodiimide solution. The hyaluronic acid was grafted onto the polyurethane outer layer catheter after being placed in a 0.9 mol / L sodium citrate solution for 6 hours, then ultrasonically cleaned with deionized water for 5 minutes and dried in a vacuum drying oven at 40°C; N,N'-dimethylaminoethylcarbodiimide reacted with the polyurethane with carboxyl groups to generate an unstable intermediate, which combined with the protonated carboxyl groups in the hyaluronic acid molecules to form an amide bond, thereby grafting the hyaluronic acid onto the polyurethane surface; the grafted distal access catheter surface had better biocompatibility;
[0057] S5. The distal access catheter prepared in S4 is sterilized with ethylene oxide to obtain a distal access catheter for neurointervention.
[0058] Comparative Example 7: Except that hyaluronic acid is not used in step S4, the remaining steps are the same as those in Example 3.
[0059] Comparative Example 8: Except that chitosan is used instead of hyaluronic acid in step S4, the other steps are the same as those in Example 3.
[0060] The catheters prepared in Example 3, Comparative Example 7, and Comparative Example 8 were cut into 0.2 cm sections along the length direction and half of the sections were flattened. The obtained catheter samples were numbered 1, 2, and 3 respectively; b End.3 cells were inoculated into a confocal culture dish and cultured for 12 hours in a BPN-150CRN carbon dioxide incubator at 37°C and 5% saturation. The cultured b End.3 cells were transferred to a DMEM culture medium (2 ml) without fetal bovine serum added with the catheter sample. After culturing in the culture medium for 3 days, the culture medium was aspirated and the catheter sample was taken out, and the surface was washed 3 times with PBS, and then fixed with 4% paraformaldehyde for 15 minutes, stained with DAPI for 10 minutes, and the staining solution was aspirated and then washed 3 times with PBS. Finally, 2 ml PBS was added and observed with a FV1200 confocal fluorescence microscope. Figure 2 This is what was observed on culture dish No. 1. It can be seen that there are a large number of cells, which indicates that the polyurethane surface modified with hyaluronic acid has good biocompatibility. Figure 3 ,4 These are the conditions observed on culture dishes No. 2 and No. 3, respectively. Figure 3 It can be found that compared with Figure 2 The number of cells was significantly reduced, indicating that its biocompatibility was poor. Figure 4 It shows that the number of cells on the surface of polyurethane modified with chitosan is still lower than Figure 2 This is mainly because the molecular weight of chitosan is too low to amino-amino the polyurethane surface well, so the biocompatibility is relatively low.
[0061] Example 4
[0062] S1. Modified polytetrafluoroethylene: 1.0 g of polyethylene oxide (PEO) was weighed and added to 40 ml of a 20% polytetrafluoroethylene emulsion, and then magnetically stirred at room temperature for 12 hours to form a mixed emulsion; the mixed emulsion was coated on the upper surface of a metal tube core rod through an electrostatic spinning machine, with a coating thickness of 50 μm, placed in an oven at 40°C for 12 hours for preliminary shaping, and then transferred to a muffle furnace at 200°C for sintering for 5 hours; after sintering, a spring layer was wrapped on the outer surface of the polytetrafluoroethylene coating, and the spring layer was formed by extruding a molten silicone rubber roller, with a thickness of 40 μm; the addition of polyethylene oxide reduced the surface properties of the polytetrafluoroethylene coating and formed a micro-nano rough structure, which improved the hydrophobicity of the inner wall of the tube;
[0063] S2. A 30um nickel-titanium alloy wire is irradiated with a laser beam to cause the metal wire to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, and at the same time improving the strength of the alloy. The laser parameters are a wavelength of 1100nm, a frequency of 100Hz, and a power of 20W. The high-intensity plasma shock wave generated by the strong laser beam is continuously applied to the surface of the nickel-titanium alloy to cause it to undergo plastic deformation, reshape the state of the alloy surface, and make it have higher strength.
[0064] S3, the outer layer of the spring layer in step S1 is reinforced by cross-weaving the nickel-titanium alloy metal coil prepared in step S2 through a braiding machine, and after reinforcement, the metal tube core rod is extruded by an online extruder, and at the same time, the surface is extruded by a pair of rollers at the rear end of the extrusion, and the molten aliphatic polyurethane outer layer is wrapped on the surface of the nickel-titanium alloy during the online extrusion, and the thickness of the polyurethane layer is 75um; the pair of rollers reduces the gaps and processing defects inside the catheter, and the combination of polyurethane and the nickel-titanium alloy coil after laser beam irradiation not only makes the catheter have good mechanical strength but also softness;
[0065] S4, hyaluronic acid grafting modification: 1.0 ml of 0.4 mmol N, N'-dimethylaminoethylcarbodiimide solution was added dropwise to 20 ml of 1.1 mol / L sodium citrate aqueous solution, and then the outer wall of the catheter prepared in step S3 was immersed in the solution, immersed at a constant temperature of 60°C for 7 hours, and then 1.0 ml of 1,3-propylenediamine was added to the solution and immersed for another 7 hours, and then the outer layer of the catheter was fully rinsed three times with deionized water. The washed catheter was placed in a vacuum drying oven at 40°C for drying. The purpose of this process is to amino the polyurethane on the outer surface; the amino outer polyurethane was immersed in 20 ml of 4 g hyaluronic acid and 1.0 ml of 0.4 mmol N, N'-dimethylaminoethylcarbodiimide solution. The hyaluronic acid was grafted onto the polyurethane outer layer catheter by immersing the catheter in a 1.1 mol / L sodium citrate solution for 7 hours, then ultrasonically cleaning the catheter with deionized water for 5 minutes and drying the catheter in a vacuum oven at 40°C. N,N'-dimethylaminoethylcarbodiimide reacted with the polyurethane with carboxyl groups to generate an unstable intermediate, which combined with the protonated carboxyl groups in the hyaluronic acid molecules to form an amide bond, thereby grafting the hyaluronic acid onto the polyurethane surface. The grafted distal access catheter surface had better biocompatibility.
[0066] S5. The distal access catheter prepared in S4 is sterilized with ethylene oxide to obtain a distal access catheter for neurointervention.
[0067] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solution described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solution to deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. A method for preparing a distal access catheter for neurointervention, characterized in that: The specific preparation method is as follows: S1. Modified polytetrafluoroethylene: weigh 0.4-1.0g of polyethylene oxide and add it to 40ml of polytetrafluoroethylene emulsion with a mass fraction of 20%, and then stir it magnetically at room temperature for 12 hours to form a mixed emulsion; apply the mixed emulsion to the upper surface of the metal tube core rod through an electrostatic spinning machine, with a coating thickness of 20-50um, place it in an oven at 40°C for 12 hours to dry it for preliminary shaping, and then transfer it to a muffle furnace at 170-200°C for sintering for 2-5 hours; after sintering, wrap a spring layer on the outer surface of the polytetrafluoroethylene coating, and the spring layer is formed by extruding molten silicone rubber rollers, with a thickness of 30-40um; S2. A 20-30um nickel-titanium alloy wire is irradiated with a laser beam to cause the metal wire to undergo a rapid melting and solidification process, thereby making the surface of the nickel-titanium alloy uniform and dense, while improving the strength of the alloy. The laser parameters are a wavelength of 1000nm, a frequency of 50Hz, and a power of 5-20W; S3, the outer layer of the spring layer in step S1 is reinforced by cross-weaving the nickel-titanium alloy wire prepared in step S2 through a braiding machine, and after reinforcement, the metal tube core rod is extruded by an online extruder, and at the same time, the surface is extruded by a pair of rollers at the rear end of the extrusion, and the molten aliphatic polyurethane outer layer is wrapped on the surface of the nickel-titanium alloy during the online extrusion, and the thickness of the polyurethane layer is 60-75um; S4. Hyaluronic acid grafting modification: add 0.4-1.0 ml of 0.1-0.4 mmol N,N'-dimethylaminoethylcarbodiimide solution to 20 ml The outer wall of the catheter prepared in step S3 is immersed in a 0.5-1.1 mol / L sodium citrate aqueous solution, and then immersed in the solution at a constant temperature of 30-60°C for 4-7 hours, and then 0.4-1.0 ml of 1,3-propylenediamine is added to the solution and immersed for another 4-7 hours, and then the outer wall of the catheter is fully rinsed three times with deionized water, and the washed catheter is placed in a vacuum drying oven at 40°C for drying. The purpose of this process is to amino the polyurethane on the outer surface; the amino outer polyurethane is immersed in 20 ml 0.5-1.1 mol / L sodium citrate solution containing 1-4 g hyaluronic acid and 0.4-1.0 ml of 0.1-0.4 mmol N, N'-dimethylaminoethylcarbodiimide solution for 4-7 hours, and then taken out and ultrasonically cleaned with deionized water for 5 minutes, and then placed in a vacuum drying oven at 40°C for drying to obtain a distal access catheter with a polyurethane outer layer grafted with hyaluronic acid; S5. The distal access catheter prepared in S4 is sterilized with ethylene oxide to obtain a distal access catheter for neurointervention.
2. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: In step S1, 0.6 g of polyethylene oxide was weighed.
3. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: The thickness of the polytetrafluoroethylene coating in step S1 is 40 um.
4. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: In step S1, sintering is performed in a muffle furnace at 200°C.
5. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: In step S2, a 30 um nickel-titanium alloy wire is used.
6. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: In step S3, the thickness of the polyurethane layer is 70 um.
7. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: In step S4, the amount of N,N'-dimethylaminoethylcarbodiimide added is 0.8 ml.
8. The method for preparing a distal access catheter for neurointervention according to claim 1, characterized in that: In step S4, the mixture is immersed at a constant temperature of 60° C. for 5 hours.
9. A distal access catheter for neurointervention prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for fine crystalline refractory metal
CN101575690A
Catheter of composite structure
CN108042897A
Method for preparing PTFE-based blood vessel support and application of PTFE-based blood vessel support
CN111388763A
Interventional catheter as well as preparation method and application thereof
CN111514433A
Nickel-titanium shape memory alloy and laser near-net forming preparation method thereof
CN114769618A